Arabic Speaking Skills Training through Intensive Program Activities for Boarding Students in Pone Village, West Limboto District - N. Hula, Ibnu Rawandhy; Yasin, Zohra; Inaku, Miskat S.; Basarata, Nurhanifa (Pusat Riset dan Inovasi Nasional, 2023)
The application of an Arabic-speaking environment for boarding students in their learning experiences obstacles such as limited social space for boarding students, and Arabic is not seen as a mother tongue. Learning Arabic in this case refers to the Ma'had curriculum in Pone Village, Kec. West Limboto. through intensive program activities for boarding students in Pone Village, Kec. West Limboto. With the application of the Muhadtsah method using various techniques, such as observation, interviews, outreach, and training. The approach used in this learning process is a humanistic approach, which places students as the center of learning, with an emphasis on their emotional, social, and psychological aspects. In addition, learning also adopts a media-based approach by using a modul pembelajaran as a learning tool. By combining these various approaches, it is hoped that students can be more actively involved in the teaching and learning process of Arabic and improve their speaking skills. The implementation of this service is in August-September 2022 with the result of the service, namely an increase in learning Arabic through the Muhadtsah Method's Speaking Skills (Maharah al-kalam) by Using a Learning modules seen from the results of the pretest and posttest scores